Cost-Effectiveness Of Midostaurin In The Treatment Of Acute Myeloid Leukemia With The FLT3 Mutation In Spain - Arenaza A; Diez R; Esteve J; Di Nicolantonio R; Gostkorzewicz J; Martínez C; Martínez Llinàs D; Martinez-Lopez J; Montesinos P; Moure-Fernández A; Sierra J; Vinent JL (Dove Medical Press, 2019)
Ainhoa Arenaza,1 Raúl Diez,2 Jordi Esteve,3 Roberta Di Nicolantonio,4 Joana Gostkorzewicz,4 Carlos Martínez,5 Diana Martínez Llinàs,6 Joaquin Martinez-Lopez,7 Pau Montesinos,8 Aída Moure-Fernández,6 Jorge Sierra,9 Joan Lluís Vinent10 1Pharmacy Department, Clínico San Carlos Hospital, Madrid, Spain; 2Pharmacy Department, University De Getafe Hospital, Madrid, Spain; 3Hematology Department, Clinic Hospital, Barcelona, Spain; 4Health Economics and Outcome Research, Novartis Farmacéutica S.A., Madrid, Spain; 5Pharmacy Department, University Hospital Araba, Vitoria, Spain; 6Oblikue Consulting, S.L., Barcelona, Spain; 7Hematology Department, University Hospital 12 de Octubre, CNIO, Complutense University, Madrid, Spain; 8Hematology Department, University Hospital La Fe, Valencia, & CIBERONC, Instituto Carlos III, Madrid, Spain; 9Hematology Department, University Hospital Santa Creu i Sant Pau, Barcelona, Spain; 10Pharmacy Department, Sant Joan de Déu Hospital, Barcelona, SpainCorrespondence: Diana Martínez LlinàsOblikue Consulting, S.L. C/Comte d’Urgell, 240, 2-D, Barcelona 08036, SpainTel +34 932521377Fax +34 93 737 9984Email diana.martinez@oblikue.comPurpose: The addition of midostaurin to standard chemotherapy (cytarabine and daunorubicin) has shown significant improvements in the survival of patients with acute myeloid leukemia with the FLT3 mutation (FLT3-AML). The objective of this study was to determine whether this intervention would be cost-effective in Spain.Methods: A partitioned survival model with five health states was developed (diagnosis and induction, complete remission, no complete remission, transplantation and death). A lifetime time horizon and the Spanish National Health System perspective were adopted. During the first three years, permanence in the different health states was determined according to the results of the RATIFY study. In successive years, the death rates of the Spanish population adjusted by a factor to reflect long-term disease-related mortality were used. Utilities were obtained from the literature. Pharmacological costs (first and second line) and the costs of other health resources (hospitalizations, visits and tests) were included. The robustness of the model was evaluated by deterministic and probabilistic sensitivity analyses.Results: The addition of midostaurin resulted in 1.46 life years gained (LYG) and 1.23 quality-adjusted life years (QALY) gained and implied an additional cost of € 47,955, resulting in an incremental cost-effectiveness ratio (ICER) of € 32,854/LYG and an incremental cost-utility ratio of € 38,985/QALY. In the univariate sensitivity analysis, the threshold of € 50,000/QALY was not exceeded in any case; taking into consideration potential discounts of 20-40% in the PVL of midostaurin the ICER would be below € 30,000/QALY, a commonly accepted threshold in Spain. In the probabilistic analysis, when the threshold was € 50,000/QALY, midostaurin was cost-effective in 82.3% of simulations.Conclusion: According to our modeling, midostaurin, in combination with standard chemotherapy, could be an efficient alternative for the treatment of FLT3-AML in Spain.Keywords: AML, modeling, efficiency, health economics, economic evaluation